2021
DOI: 10.1111/imm.13424
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of IL‐26 to pave a new way for a profound understanding of the pathobiology of cancer, inflammatory diseases and infections

Abstract: Cytokines are considered vital mediators of the immune system. Down-or upregula-How to cite this article: Gowhari Shabgah A, Abdelbasset WK, Sulaiman Rahman H, Bokov DO, Suksatan W, Thangavelu L, et al. A comprehensive review of IL-26 to pave a new way for a profound understanding of the pathobiology of cancer, inflammatory diseases and infections. Immunology. 2022;165:44-60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Immunohistochemical results of AIH liver specimens confirm a significant accumulation of IL‐26 spatially distributed in liver portal areas and lesions of interface hepatitis. Studies have revealed the multiple cellular sources of IL‐26, including T cells, natural killer (NK) cells, NKp30 + γδT cells, CD68 + macrophages and, more recently, lung mucosal‐associated invariant T (MAIT) cells 31,33,34 . In our study, in situ confocal staining speculated that CD4 + T cells, CD8 + T cells and CD68 + macrophages in AIH represent hepatic reservoirs of IL‐26.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Immunohistochemical results of AIH liver specimens confirm a significant accumulation of IL‐26 spatially distributed in liver portal areas and lesions of interface hepatitis. Studies have revealed the multiple cellular sources of IL‐26, including T cells, natural killer (NK) cells, NKp30 + γδT cells, CD68 + macrophages and, more recently, lung mucosal‐associated invariant T (MAIT) cells 31,33,34 . In our study, in situ confocal staining speculated that CD4 + T cells, CD8 + T cells and CD68 + macrophages in AIH represent hepatic reservoirs of IL‐26.…”
Section: Discussionmentioning
confidence: 71%
“…17,21,22 For instance, exogenous IL-26 injection augmented Th2-like immune response in the oxazoloneinduced atopic dermatitis murine model 22 and IL-26-induced Th17-type inflammation exacerbated murine sepsis. 30 In contrast with the view that IL-26 is related to disease progression, 31 a pioneer study revealed the therapeutic implication of IL-26. 32 Dextran sodium sulfate (DSS)challenged humanized IL-26 transgenic (hIL-26Tg) mouse exhibited lower inflammatory score and was henceforth protected from acute colitis.…”
Section: Discussionmentioning
confidence: 99%
“…IL-26 directly binds neutrophil-derived extracellular DNA to facilitate intracellular inflammation signaling in a stimulator of interferon genes (STING)- and inflammasome-dependent manner ( 5 ). It is possible that an enhanced neutrophilic immune response through IL-26 after the vaccination may have been responsible for the ANCA-associated glomerulonephritis in our case.…”
Section: Discussionmentioning
confidence: 99%
“…AAV is a multisystem autoimmune disease, with neutrophil extracellular traps (NETs) involved in its pathogenesis ( 4 ). Interleukin (IL)-26 is a member of the IL-10 family of cytokines that participates in inflammatory signaling through directly binding DNA to facilitate cellular transduction and intracellular inflammation signaling ( 5 ). Recently, it has been shown that IL-26 binds to NETs to induce the secretion of inflammatory cytokines (IL-1β and IL-6) and chemokines (IL-8) by myeloid cells in ANCA-associated glomerulonephritis ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a classification based on the similarity of receptor compartments and structures, cytokines are divided into four major groups: (i) type I cytokines (comprised of interleukins (IL)-2, IL-3, IL-4, IL-5, IL-6, IL-7, IL-8, IL-9, IL-11, IL-12, IL-13, and IL-15), (ii) type II cytokines (including interferons (IFNs) and the IL-10 superfamily), (iii) tumor necrosis factor (TNF) superfamily (TNFs, Fas ligands, etc. ), and (iv) immunoglobulin (Ig) superfamily (IL-1/IL-18) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%